2020
DOI: 10.1097/aud.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Electrocochleography: Analysis of Real-Time Recordings

Abstract: Objectives: Real-time electrocochleography (ECochG) has been used as a monitoring tool during cochlear implantation (CI), whereby, amplitude drops have been correlated with postoperative acoustic hearing results. However, no consensus has been reached as to how a single event of an amplitude drop should be characterized. The aim of this study was to identify ECochG events that predict loss of hearing 1 month after surgery. Design: Fifty-five patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…In our figures, the relative signal recovery after an ECochG event was not linearly correlated to the acoustic hearing outcome. This corroborates earlier findings (3). In contrast to that, Campbell et al (1) described better acoustic hearing results, if CM amplitudes recovered after an amplitude drop.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our figures, the relative signal recovery after an ECochG event was not linearly correlated to the acoustic hearing outcome. This corroborates earlier findings (3). In contrast to that, Campbell et al (1) described better acoustic hearing results, if CM amplitudes recovered after an amplitude drop.…”
Section: Discussionsupporting
confidence: 91%
“…Measurement setup and data collection was identical with the method described in our previous article (3). In short, an Etymotics ER3A transducer (3 M, USA) and E-A-RLINK Foam Ear Tip 3B (3 M, USA) delivered the acoustic stimuli (tone pip at 500 Hz with alternating polarities).…”
Section: Electrocochleographymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the sometimes rapid ECochG fluctuations seen here are not often observed in extracochlear ECochG recordings ( 3 ), where very different patterns of ECochG amplitude loss and recovery are encountered. It is clearly argued in Weder et al ( 19 ) that these transient drops have just as significant an effect on postoperative hearing preservation as permanent drops. It seems likely, therefore, that the observations made here may not be directly applicable to the extracochlear ECochG approaches.…”
Section: Discussionmentioning
confidence: 95%
“…A randomized study showed that when the CM amplitude decreased by 30% or more (related to the initial maximum amplitude), a slight withdrawal of the electrode resulted in a significant improvement of postoperative residual hearing 21 . However, the definition of a detrimental drop is unclear; another publication reported a CM decrease of 61% (or more) at a slope steepness of 0.2 µV/ s (or more) to be significant 9 . A drop in ECochG responses may also be due to other causes, such as the interaction of different signal generators, passing the 500 Hz range within the cochlea, or contact of the basilar membrane with the electrode array 6 , 24 .…”
Section: Discussionmentioning
confidence: 99%